Study of the Physical, Environmental, and Economic Sustainability of Purwosari Agrotourism in Semarang City - Azmi, Hafzhi Nur; Rahmanda, Taufan (ASTONJADRO, 2025)
Agrotourism has been one of the most rapidly developing sectors in the last two decades and is predicted to continue growing in the future. The pandemic is claimed to have had no significant impact on the development and growth of the agrotourism sector. However, Agrotourism Purwosari, a leading agrotourism destination in Semarang City, has not yet optimized its potential. This is indicated by suboptimal management and various restrictions during the pandemic that have decreased its performance. These challenges have the potential to disrupt the sustainability of agrotourism. This study aims to examine the sustainability of agrotourism with a focus on Agrotourism Purwosari, which is managed by the Semarang City Agriculture Office. This research uses a mixed-methods approach, including descriptive statistical analysis to identify the characteristics of agrotourism, and scoring analysis to assess sustainability efforts through a questionnaire distributed to all managers. Additionally, a qualitative descriptive analysis was conducted through in-depth interviews with four key actors. Based on the analysis, it is found that Agrotourism Purwosari is classified as Moderately Sustainable (3.37), with social and cultural sustainability being quite dominant, but still weak in business performance sustainability.